2017
DOI: 10.1002/ijc.30882
|View full text |Cite
|
Sign up to set email alerts
|

Association between age‐related reductions in testosterone and risk of prostate cancer—An analysis of patients' data with prostatic diseases

Abstract: The relationship between serum total testosterone and prostate cancer (PCa) risk is controversial. The hypothesis that faster age-related reduction in testosterone is linked with increased PCa risk remains untested. We conducted this study at a tertiary-level hospital in southeast of the US, and derived data from the Medical Registry Database of individuals that were diagnosed of any prostate-related disease from 2001-2015. Cases were those diagnosed of PCa and had one or more measurements of testosterone prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 35 publications
0
15
0
3
Order By: Relevance
“…If age‐related decline in testosterone is risky for the initiation of PCa, weight gain during middle‐to‐late adulthood may alter the testosterone‐estrogen balance due to aromatization of testosterone to estradiol, speeding up testosterone decline . Recent studies on the dynamic change in testosterone levels provided direct evidence supporting a new mechanism for PCa: quicker‐than‐normal declines in testosterone with age would increase PCa risk. Besides sex hormones, other mechanisms relating weight gain during middle‐to‐late adulthood to PCa risk include insulin, insulin‐like growth factor‐1 (IGF‐1), leptin, and various inflammatory mediators; further research at the macropopulation level to understand these mechanisms is needed.…”
Section: Discussionmentioning
confidence: 99%
“…If age‐related decline in testosterone is risky for the initiation of PCa, weight gain during middle‐to‐late adulthood may alter the testosterone‐estrogen balance due to aromatization of testosterone to estradiol, speeding up testosterone decline . Recent studies on the dynamic change in testosterone levels provided direct evidence supporting a new mechanism for PCa: quicker‐than‐normal declines in testosterone with age would increase PCa risk. Besides sex hormones, other mechanisms relating weight gain during middle‐to‐late adulthood to PCa risk include insulin, insulin‐like growth factor‐1 (IGF‐1), leptin, and various inflammatory mediators; further research at the macropopulation level to understand these mechanisms is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Massengil et al [23] showed that PCA patients with non-organ-confined disease after RP (pT3-T4) had significantly lower pretreatment total testosterone (TT) levels than those with organ confined cancer (pT1-T2). In addition, Wang et al [24] showed that patients with an annual testosterone reduction of more than 30 ng/dL had a nearly 5-fold increase in PCA risk. Moreover, recent evidence in the literature has demonstrated that low baseline serum levels of free testosterone are associated with an increased risk of high-grade PCA [25] as well as adverse pathologic features, functional outcomes, and biochemical recurrence [26].…”
Section: Discussionmentioning
confidence: 99%
“…This results in an overall hyper-stimulation of luminal glandular cells despite a decrease in TT serum levels. This prostatic cell hyper-stimulation results in DNA damage and uncontrolled luminal cell AR-driven proliferation [24]. These alterations constantly select newer and progressively more aggressive prostatic cellular clones.…”
Section: Discussionmentioning
confidence: 99%
“…Because PCa is highly incident and few preventive strategies currently exist, elucidation of a benefit of statins in preventing PCa could confer a considerable significance in public health. Clarifying the statin‐PCa association may also cast light to elucidate the steroid hormone mechanism connecting metabolic disorders with prostate carcinogenesis …”
Section: Introductionmentioning
confidence: 99%
“…Clarifying the statin-PCa association may also cast light to elucidate the steroid hormone mechanism connecting metabolic disorders with prostate carcinogenesis. 7,8 Statin use has been reported to be negatively correlated with advanced PCa risk, [9][10][11] but evidence for the associations of statin use with overall PCa remains mixed [9][10][11][12][13] and with Gleason score-specific PCa is rare. Reasons for such a varying observation are not clarified but may result from a detection bias ("healthy user bias").…”
Section: Introductionmentioning
confidence: 99%